Growth hormone response to arginine test differentiates between two subgroups of Huntington's disease patients. Issue 5 (30th September 2010) - Salvatore, Elena; Rinaldi, Carlo; Tucci, Tecla; Di Maio, Luigi; Di Somma, Carolina; Savastano, Silvia; Lombardi, Gaetano; Filla, Alessandro; Colao, Annamaria; De Michele, Giuseppe
Abstract : Objective: Huntington's disease (HD) is an autosomal dominant disorder characterised by motor, cognitive and psychiatric disturbances. Several studies have demonstrated that hypothalamic dysfunction is part of the phenotypic spectrum. The aim of the study was to evaluate the growth hormone (GH) response to arginine infusion in a cohort of HD patients, to search for an in vivo biomarker of hypothalamic dysfunction. Methods: The authors investigated 17 HD patients and 17 age-, sex- and BMI-matched healthy controls. Clinical assessment of patients was performed using the Unified Huntington's Disease Rating Scale motor section and total function capacity. Metabolic and endocrine investigations included total, LDL and HDL cholesterol, basal insulin, GH, insulin-like growth factor 1 (IGF-1), SD Score IGF-1 (SDS IGF-1) and the GH response to arginine stimulation. Results: HD patients showed lower plasma IGF-1 and SDS IGF-1 levels and a higher baseline GH in comparison with control subjects. The arginine test induced a normal GH peak in nine patients (53%; Arg+), whereas the response was absent in the remaining eight (47%; Arg–). Arg+ and Arg– also showed two distinct endocrine/metabolic profiles with differences in insulin and lipid metabolism. Conclusion: It remains to be clarified if these two subgroups of patients, according to the GH response to arginine, correspond to different disease stages or to different patterns of neurodegeneration.